2009
DOI: 10.1245/s10434-009-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Matrilysin Levels Predict Outcome in Curatively Resected Colorectal Cancer Patients

Abstract: MMP-7 predicts recurrence in curatively resected CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
1
16
1
Order By: Relevance
“…Moreover, they showed MMP-7 to be an independent prognostic factor for survival in patients with advanced CRC. On the other hand, Martinez-Fernandez et al [37], found not only the correlation between increased serum level of MMP-7 and worse prognosis, but also revealed that MMP-7 predicts recurrence in curatively resected CRC patients. Additionally, similarly to our observations, they noted high serum level of MMP-7 in older CRC patients.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, they showed MMP-7 to be an independent prognostic factor for survival in patients with advanced CRC. On the other hand, Martinez-Fernandez et al [37], found not only the correlation between increased serum level of MMP-7 and worse prognosis, but also revealed that MMP-7 predicts recurrence in curatively resected CRC patients. Additionally, similarly to our observations, they noted high serum level of MMP-7 in older CRC patients.…”
Section: Discussionmentioning
confidence: 98%
“…In 2016, Niedworok and his colleagues' findings also showed elevated serum levels in metastatic compared to non-metastatic RCC cases (19). Thus, MMP-7, in addition to carbonic anhydrase IX, VEGF, IL-6 and CRP, may serve as a promising serum marker for the detection of metastasis and prediction of poor survival for RCC, similarly to other cancers including gastric (22), colorectal (23,24) and ovarian cancer (25). There are several limitations in this study.…”
Section: Discussionmentioning
confidence: 75%
“…In cancer immunology, a clear role of MMP7 and of other MMPs has been shown in tumour growth and invasion (17,(20)(21)(22)(23)(24)(25). Increased MMP7 expression in tumour tissue, serum, lymph nodes and peritoneal liquid generally correlates with worse prognosis, a tendency for metastatic disease and reduced overall survival (18,(26)(27)(28)(29)(30)(31)(32). This suggests a possible role for MMP7 in the determination of locally advanced cancer in resected specimens, and in staging and planning for eventual adjuvant therapy, attesting to a potential role of MMP7 as prognostic factor and tumour marker (33) The effect of RT on MMP7 gene in human rectal cancer was first investigated in vivo by Kumar et al, who observed overexpression of MMP7 in radiated rectal cancer tissue compared to nearby irradiated normal rectal tissue (9).…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the fragility and poor staining of the specimens from such patients, whereby only five cases were accepted for examination. Given the role of MMP7 in abnormal tissue remodelling after RT injury (9,25,29) and its relation to progressive and metastatic colorectal disease, it may be rational to use potential preventive or therapeutic specific tissue inhibitors of MMPs with RT.…”
Section: Discussionmentioning
confidence: 99%